ASPECTS OF PEDAGOGICAL CULTURE AS COMPONENT OF PROFESSIONAL COMPETENCES OF THE FUTURE TEACHER - E.A. Annyuk (Academy of Cognitive and Natural Sciences, 2022)
The article is dedicated to outhlook of pedagogical culture and its components as an important aspect of forming of future teacher's professional authority.